Possible Association of Interleukin-31/-31RA Signalling and Basophils with Itch in Porokeratosis - Satoshi Okuno; Takashi Hashimoto; Riichiro Sugiura; Takahiro Satoh (Acta Dermato-Venereologica, 2023)
Abstract is missing (Short communication)